Critical Analysis Of Sonnet 12 By William Shakespeare (Diversity Research: Journal of Analysis and Trends, 2025)
illiam Shakespeare's Sonnet 12 is one of the most striking examples of the poet's reflections on time, aging, and the inevitability of loss. The article provides a critical analysis of this work, examining the main themes, images, and artistic techniques used by the author. Particular attention is paid to the symbolism of nature, the contrast between the temporality of human life and the eternity of art, as well as the philosophical subtext of the sonnet